The Yorkists : the History of a Dynasty. - Crawford, Anne (Bloomsbury Publishing PLC, 2007)
The Yorkist dynasty includes both the most wicked king in English history, Richard III, and the most tragic, his nephew Edward V, one of the Princes in the Tower. They came to the throne in 1461, when Edward IV, who traced his claim to Edward III, replaced the ineffectual Henry VI as king. Forced into exile in 1470, Edward returned to power after the bloody battle of Towton in 1470 finally ended Lancastrian opposition. His reign was ended by his premature death in 1483, leaving behind his son Edward, a minor, as his heir. This led to Richard III's usurpation, ended two years later by his defea.